DENISE ALVES FUNGARO: A GREAT INSPIRATION IN CHEMISTRY - Assis Faustino, Gustavo Augusto (Revista da Associação Brasileira de Pesquisadores/as Negros/as (ABPN), 2020)
Denise Alves Fungaro was born in São Paulo in 1959, coming from a family of simple origin and humble condition. Since childhood, her attention and curiosity have been aroused by chemistry and, at school, her interest in this science has increased significantly. She took a pre-university course and in 1978 started her undergraduate degree in Chemistry at the University of São Paulo (USP). She graduated in 1983 and entered her master’s degree at USP, completing it in 1987. In the following year, she entered the doctorate also at USP, finishing it in 1993. She is currently the coordinator of research projects focusing mainly on the development of value-added materials from waste, optimization of the green roof and addition of waste in cementitious matrix. A highly awarded researcher, Denise is also part of the study group entitled "Planetary Health" from the Institute of Advanced Studies of the University of São Paulo (IEA-USP).